Pengembangan Bahan Ajar Menulis Berita pada Siswa SMP Kelas VIII - Luise Nenis Putri Mega Marta; Mursalim; Bibit Suhatmady (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
The learning process using teaching materials is an effective way for teachers to deliver material to students. This study's teaching materials' development aims to produce teaching materials for writing news texts on eighth-grade junior high school students. The developed teaching material validity is seen from developing, implementing and measuring the effectiveness of the teaching material. The research method used is the Borg and Gall's Research and Development. Data collection techniques used were questionnaires and observations. Data analysis uses descriptive qualitative analysis and descriptive statistical analysis. The process of developing the materials was based on experts' validation of the materials, the language, and the product's graphic. The material experts' validation result showed a value of 77.5% and 92.5% in the very feasible category. The linguists' validation results showed a value of 72% and 92% in the very feasible category. The graphic experts showed a value of 78% and 92.8% included in the very feasible category. In this study, the product trial subjects were students of class VIII of junior high school and were carried out with small class trials and field trials. Through a small group and field test results, the effectiveness of teaching materials from assessing student responses was the average value of 3.23 (82.8%) on average value or good category. Student learning outcomes show an overall grade point average of 83.8 (100%). This shows that the quality of student learning based on teaching materials in writing news is very good. From the data obtained, the developed teaching materials are suitable for use.